MEKTEPKE SHEKEMGI TÁRBIYA JASÍNDAǴÍ BALALARDÍŃ HÁREKET ISKERLIGIN ASÍRÍWDÍŃ ZAMANAGÓY PEDAGOGIKALÍQ TEXNOLOGIYALARÍ - Toylibaev, S.M.; Allambergenova, R.D. (SCIENCE and SOCIETY, 2023)
This article deals mainly with the physical development of preschool children. The study of the issues of the comprehensive physical development of preschool children is an investment in the future, because the future generation of the country is a reliable foundation for the future of the whole country and the whole nation as a whole.